High precise dating on the variation of the Asian summer monsoon since 37 ka BP - Li, Ting-Yong (2021)
Comprehensive comparison of paleoclimate change based on records constrained by precise chronology and high-resolution is essential to explore the correlation and interaction within earth climate systems. Here, we propose a new stalagmite-based multidecadal resolved Asian summer monsoon (ASM) record spanning the past thirty-seven thousand years (ka BP, before ad 1950) from Furong Cave, southwestern China. This record is consistent with the published Chinese stalagmite sequences and shows that the dominant controls of the ASM dynamics include not only insolation and solar activity but also suborbital-scale hydroclimate events in the high latitudes of the northern hemisphere, such as the Heinrich events, Bølling-Allerød (BA), and Younger Dryas (YD). Benefit from the unprecedented accurate chronology, the timings of these events are precisely dated, with uncertainties of, at most, 40 years (2σ). The onset of the weak ASM during the YD began at 12.92 ka BP and lasted for 430 years. The occurrence of the 200-yr Older Dryas during the BA period was dated from 13.87 to 14.06 ka BP. The durations of the three Heinrich (H) events, H1, H2, and H3, are 14.33–18.29, 23.77–24.48, and 28.98–30.46 ka BP, respectively. Furong record shows surprisingly variable onset transitions of 980, 210, and 40 years for the corresponding weak ASM events. These discrepancies suggest different influences of the H events on ASM dynamics. During the periods of H 1–3, the obvious difference between our Furong record and NGRIP δ18O record indicated the decoupling correlation between the mid-low latitudes and high latitudes. On the other hand, synchronous climate change in high and low latitudes suggests another possibility which different to the dominant role of Northern high latitudes in triggering global climate change. Our high quality records also indicate a plausible different correlation between the high and mid-low latitudes under glacial and inter-glacial background, especially for the ASM regimes.